1985
DOI: 10.1093/jn/115.7.944
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Restriction on Liver Protein Synthesis in Rats

Abstract: At 6 wk of age, male Fischer F344 rats were fed a purified, casein-based diet either ad libitum or in the amount of 60% of the diet consumed by the rats fed ad libitum (restricted diet). Hepatocytes were isolated from the rats between 2.5 and 19 mo of age. The protein content of the hepatocytes isolated from the rats fed the restricted amount of diet was significantly lower than that of hepatocytes isolated from rats fed ad libitum. The DNA and RNA content of the hepatocytes were similar for the rats fed the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1989
1989
2014
2014

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…Furthermore, when expressed as a fractional synthesis rate (FSR, %/d) assuming that valine protein content in the sheep liver was equal to 520 nmol of valine/mg of protein (MacRae et al, 1993), the protein synthesis, measured by incorporation of [U-14 C]valine into the liver slices, ranged from 2 to 10%/d in our experimental conditions. These values are less than in vivo values for the FSR of hepatic proteins in ruminants (20%/d, Lobley et al, 1994) but are consistent with values obtained in incubated hepatocytes (FSR = 11%/d; Birchenall-Sparks et al, 1985). Last, gluconeogenesis was less in our study compared with values usually found in vitro (Donkin and Armentano, 1993).…”
Section: The Incubated Liver Slices: Methodological Aspectssupporting
confidence: 85%
See 1 more Smart Citation
“…Furthermore, when expressed as a fractional synthesis rate (FSR, %/d) assuming that valine protein content in the sheep liver was equal to 520 nmol of valine/mg of protein (MacRae et al, 1993), the protein synthesis, measured by incorporation of [U-14 C]valine into the liver slices, ranged from 2 to 10%/d in our experimental conditions. These values are less than in vivo values for the FSR of hepatic proteins in ruminants (20%/d, Lobley et al, 1994) but are consistent with values obtained in incubated hepatocytes (FSR = 11%/d; Birchenall-Sparks et al, 1985). Last, gluconeogenesis was less in our study compared with values usually found in vitro (Donkin and Armentano, 1993).…”
Section: The Incubated Liver Slices: Methodological Aspectssupporting
confidence: 85%
“…This absence of hormones and the decreased concentrations of nutrients in the incubation medium aimed to avoid any direct stimulation of the metabolic pathways measured. This approach is novel because the vast majority of studies using liver slices or hepatocytes have used supraphysiological concentrations of nutrients (Birchenall-Sparks et al, 1985;Pocius and Herbein, 1986;Mutsvangwa et al, 1996;Overton et al, 1999). Because the concentrations of nutrients used in our experiment are less than those reported in the literature, the viability of the liver slices during the incubation period needed to be checked.…”
Section: The Incubated Liver Slices: Methodological Aspectsmentioning
confidence: 99%
“…However, in some organs with rapidly dividing cells, apoptosis actually increases during CR, for example, in the liver (James et al 1998) and the gut (Holt et al 1998). This increase, along with the known shrinkage of cells during CR (Birchenall-Sparks et al 1985), may both contribute to the down-sizing of these organs in the restricted animal. The increased rate of apoptosis may minimize the risk of cancer during CR (James et al 1998).…”
Section: Links Between Cr Aging and Apoptosismentioning
confidence: 99%
“…This can be achieved through increasing synthesis or degradation of macromolecules. DR prevents the age-related decline in protein synthesis [190, 191] and increases macromolecular breakdown by autophagic [192, 193] and proteasomal degradation [194203]. DR also increases DNA repair activity [91, 204207], which may reduce DNA oxidation, and reduces DNA mutations [27, 183185].…”
Section: Effects Of Dietary Restriction On Oxidative Stress During Agingmentioning
confidence: 99%